Tratamiento legal de las criptomonedas en Colombia 2009-2020 (2020)
Since the emergence of Bitcoin by Satoshi Nakamoto in 2009, the cryptocurrency network has been developed, based on peer-to-peer networks, to evolve to Block chain technology. This cryptocurrency in 10 years has managed to move from a market value of $ 0.003 in April 2010 to $ 9.619 in may 2020, becoming the most valuable cryptocurrency in the market with a total of $ 184,641,829,734 as of may 18 of 2019, and its price is expected to continue rising. The behavior of this cryptocurrency is of legal interest because the resources of the legal banking system are migrating to this destination, and it is necessary to elucidate what is the treatment that should be taken on the ownership of this and the derivative transactions. This project seeks to establish a definition of the type of good that is a cryptocurrency in Colombian legislation, and present the regulatory framework that supports it to date. To concretize, once analyzed the national normativity as international and the technological advances around cryptocurrency (Blockchain), it can be concluded that its concept was being incorrectly related, since it is not a legal tender, but is an intangible asset that is part of the heritage of a natural or legal person, making it tradable and negotiable in the exchange of goods and services.